High-speed rail accessibility: a comparative analysis of urban access in Los Angeles, San Francisco, Madrid, and Barcelona - Zhong, Chuyuan; Bel, Germà; Warner, Mildred E. (European Journal of Transport and Infrastructure Research, 2014)
This paper is intended to set the context for policy discussion on HSR feasibility from the perspective of station accessibility. We compare the proposed Los Angeles – San Francisco HSR corridor to the functioning HSR line between Madrid and Barcelona to assess relative station accessibility based on urban structure. Our methodology assesses socioeconomic and spatial characteristics of mono-centric versus polycentric cities that may affect HSR accessibility. By addressing challenges of unit (urban geography), data series (normalization) and identifying four key components of HSR attractiveness (population, population density, income and employment) we have created a methodology that allows us to assess relative station accessibility in the four compared metropolitan areas. We find urban structure limits the potential accessibility of HSR in the California context, and warn HSR planners they should proceed with caution.